PENGARUH PEMBERIAN JUS BUAH KERSEN (Muntingia calabura) TERHADAP KADAR TRIGLISERIDA PADA TIKUS SPRAGUE DAWLEY DISLIPIDEMIA - , RISNHUKATHULISTIWI MAGHRIBI, Dr. Med dr. Indwiani Astuti ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Coronary heart disease is caused by the interruption of blood flow to the heart muscle because there is a narrowing of the coronary arteries or atherosclerosis. The cause of atherosclerosis is dyslipidemia. One of the abnormalities dyslipidemia is hypertriglyceridemia. Antioxidants play a role in dealing hypertriglyceridemia. One type of antioxidant is vitamin C. Vitamin C can reduce hypertriglyceridemia with different mechanisms. One of the fruits that rich vitamin C are cherry (Muntingia calabura). Thus conducted this study on the influence of fruit cherry (Muntingia calabura) on the incidence of dyslipidemia, especially its effect on blood triglyceride levels. Objective: To determine the effect of cherry juice (Muntingia calabura) to triglyceride of Sprague Dawley rats dyslipidemia. Methods: This research is a quasi experimental study with pretest and posttest control group design. 25 rats were divided into 5 groups underwent an adaptation period of 7 days (pre-test), a high-fat diet period of 5 weeks (mid-test) and the treatment period of 2 weeks (post-test). At the treatment period, rat divided into 5 groups, K1, K2, K3, K4 and K5. K1/diseased control treated with the standard feed and distilled water, K2 treated with the standard feed and cherry juice dose 1 (1,15 g/mL/200 g rat weight), and K3 treated with the standard feed and cherry juice dose 2 (2,3 g/mL/200 g rat weight), K4 treated with high fat diet and cherry juice dose 2 (2,3 g/mL/200 g rat weight), and K5/normal control treated with the standard feed and distilled water. The data were analized with One Way ANOVA and Paired Sample T test after normalized data with Saphiro Wilk test. Results: There was a significant weight gain in all groups at week giving a highfat diet (p<0,05) and tended to decline during the administration cherry fruit juices especially the K2, K3, and K5. There is no significant difference in feed intake in all groups except in the 3rd week of giving high-fat diet (p<0,05). There is the effect of high-fat diet on levels of triglycerides mid test (p<0,05) although the increase is not significant (p>0,05). There is no treatment effect on triglyceride levels post-test (p>0,05) despite a significant decrease in all groups (p<0,05). Conclusion: The fruit juice cherry (Muntingia calabura) can decrease triglyceride levels of Sprague Dawley rats dyslipidemia